319 C-REACTIVE PROTEIN CONCENTRATION IS NOT AFFECTED BY ISOCALORIC DIETARY FAT REDUCTION. (1st January 2005) - Koren, M. S.; Breen, P. A.; Yang, P.; Callahan, H. S.; Matthys, C. C.; Weigle, D. S.
Abstract : Background: Consumption of a high-fat diet is associated with the development of insulin resistance and obesity. Both conditions are pro-inflammatory states characterized by increased concentrations of plasma C-reactive protein (CRP), interleukins, and TNF-alpha. However, it is unclear whether dietary fat content by itself has an effect independent from weight change on markers of inflammation. We examined plasma CRP levels in healthy volunteers who sequentially consumed a weight-maintaining moderate fat diet, an isocaloric low fat diet, and an ad libitum low fat diet. Subjects and Methods: We studied 16 subjects, 45±13 years old, 2M/14F, who were weight-stable for at least 3 months before enrollment. The mean weight of subjects was 74.9 ± 10.2 kg, BMI 27.1 ± 2.3 kg/m2. The weight-maintaining moderate fat diet consisted of 35% fat, 45% carbohydrate, and 20% of energy as protein. After consuming this diet for 2 weeks, subjects were switched to an isocaloric low fat diet consisting of 15% fat, 65% carbohydrate, and 20% protein for another 2 weeks. For the final 12 weeks of the study, subjects consumed the low fat diet ad libitum. All meals were prepared in the clinical research center and consisted of typical food items. Subjects maintained the same level of physical activity throughout the study. At the end of each diet phase, two blood samples were collected at 0800h 24 hours apart and the average CRP was measured by a high sensitivity CardioPhase hsCRP assay (Dade Behring Inc., Deerfield, IL, USA). The study had 80% power to detect a 30% change in CRP concentration between the isocaloric moderate fat and low fat diets with type I error of 0.05. Data analysis was performed with repeated measures ANOVA using SPSS software. Results: The weight of the subjects remained unchanged during the first 4 weeks of the study. The plasma CRP concentrations after 2 weeks on the weight-maintaining 35% fat diet and 2 weeks on the isocaloric 15% fat diet were not significantly different (mean ± SD were 2.49±2.79mg/L and 2.97±3.65 mg/L, respectively). Three months of ad libitum low fat diet resulted in a 4±2 kg weight loss associated with a downward trend in CRP concentration to 2.15±2.47 mg/L (p=0.11). Conclusion: Without concurrent diet-induced weight loss, weight-maintaining isocaloric 35% fat diet and 15% fat diet for 2 weeks had no significant effect on plasma CRP concentration of modestly overweight subjects.